Permanence pending: how young Chinese temporary migrants hope to stay in the UK. (2018) - Yu, Candice Hiu-Yan
Drawing on 30 in-depth qualitative interviews, this article examines the aspirations, constraints and abilities of young, highly educated, lower-middle and middle-class Chinese would-be-permanent migrants in the hope of prolonging their stay in the UK. It discusses the immigration and employment barriers, and stringent time-constraints that temporary migrants from China and Hong Kong face. This article argues that despite possessing adequate economic and cultural capital, and limited social capital, these migrants turn to marriage migration, the deployment of sexual capital, and the discourse of love as effective immigration strategies to achieve higher employability, better life chances and longer residence. This article emphasises migrants' agency, and the highly contextual nature of sexual relations in transnational migration, which blurs the boundaries of love and sex-for-visa arrangement.